NEEDS ANALYSIS ON IJEN GEOPARK MODULE FOR GEOPARK AMBASSADORS AT SMPN 3 BANYUWANGI - Hera Dwi Oktaviani; Tri Mulyati; Wageyono (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
The aims of this study was: To find out whether there is or not a gap between the ideal condition and real condition of Geopark module used by geopark ambassadors at SMPN 3. This study used descriptive qualitative method. Total respondents of this reserach were 20 students consisting of 10 female and 10 male. The procedure of this study was that researchers give questionnaires consist of idel condition and real condition to the geopark ambassadors by using google form. The results of this study showed that: in ideal condition,students expected that the module must be interesting,easy to understand and based on their desires. In real condition, 17 students or about 85% of students answered